Nurses’ competence in recognition and management of delirium in older patients: development and piloting of a self-assessment tool - Hoch, Jonas; Bauer, Jürgen M.; Bizer, Martin; Arnold, Christine; Benzinger, Petra (BMC geriatrics, 2022)
Delirium is a common condition in elderly inpatients. Health care professionals play a crucial role in recognizing delirium, initiating preventive measures and implementing a multicomponent treatment strategy. Yet, delirium often goes unrecognized in clinical routine. Nurses take an important role in preventing and managing delirium. This study assesses clinical reasoning of nurses using case vignettes to explore their competences in recognizing, preventing and managing delirium.
Gesehen am 24.01.2023